Measures against heat stress in the city of Gelsenkirchen, Germany - Dütemeyer, Dirk; Barlag, Andreas-Bent; Kuttler, Wilhelm; Axt-Kittner, Ulrich (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
In the near-surface atmosphere, heat waves during the summer cause situations that may lead to human-biometeo-rological impairment. Because of their high population density, overheated cities are particularly strongly affected by heat stress. In the future, due to the effects of climate change, heat stress will increase in terms of its intensity and spatial expansion in the areas of concern. Taking the example of the city of Gelsenkirchen, Germany, this article presents a method for the identification of areas requiring adaptation or protection. A scenario of the future increase of heat stress events is presented, based on data of the German climate change model STAR II. For the identification of areas requiring adaptation and protection, spatial analyses of the urban heat island, land use and demographic aspects were performed using GIS tools. The application and assessment of adaptation measures is investigated for an urban quarter using the microscale numerical model ENVI-met. Finally adaptation measures in urban planning against heat stress are discussed. The relevant urban planning adaptation measures, which are also important in view of climate change, not only involve heat stress reduction in the residential areas already affected, but also in-volve the protection and optimisation of existing favourable and compensation areas.